Kesiapan Infrastruktur Pendukung pada Destinasi Wisata dalam Mewujudkan Sustainable Tourism Development: The Readiness of Supporting Infrastructure for Tourism Destination in Achieving Sustainable Tourism Development - Desy Yuliana Dalimunthe; Devi Valeriani; Fitra Hartini; Rulyanti Susi Wardhani (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
For tourism destinations, infrastructure is included as natural resources and man-made resources are natural resources and man-made resources that are needed by tourists when traveling to a tourist destination. This research focuses on the readiness of social, economic, and environmental infrastructures available in tourism destinations. This research aims to analyze the readiness of supporting infrastructure in tourism destinations to achieve Sustainable Tourism Development in Bangka Island for today and the future. This research used an analysis model of IPA (Importance Performance Analysis) to measure the level of one's importance for the performance of other parties. A person's interest was measured by comparing the level of expectation with the performance that carried out using a Likert scale. This research also discussed the extent of tourists' perceptions of the interests or expectations regarding the readiness of supporting infrastructure in the destinations to achieve Sustainable Tourism Development on Bangka Island. a total sample of 240 respondents spread across two selected tourist destinations for each Regency on Bangka Island. This research provides results that the types of infrastructure in Bangka Regency and South Bangka Regency are the concentrate here, such as the economic and social infrastructures, whereas in Central Bangka Regency, the infrastructure that becomes the concentrate here including economic, social, and environmental infrastructures, especially from waste management.